2019
DOI: 10.3399/bjgp19x703877
|View full text |Cite
|
Sign up to set email alerts
|

The influence of training experiences on career intentions of the future GP workforce: a qualitative study of new GPs in England

Abstract: BackgroundThe capacity of the UK GP workforce has not kept pace with increasing primary care workloads. Although many doctors successfully complete GP specialty training programmes, some do not progress to work in NHS general practice.AimThis article explores the training experiences and perceptions of newly qualified GPs to understand how their education, training, and early experiences of work influence their career plans.Design and settingA qualitative study of doctors in their final year of GP training (ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…To date, more attention has been focused on other stages of the GP recruitment pipeline,29 but it is important that the experiences GP trainees encounter during their secondary care placements are also considered as a potential source of discontent. On this point, our findings add to those of Spooner et al , whose research on career intentions of new UK GPs found that many felt that hospital placements had done ‘little to prepare them for GP work’ 12…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…To date, more attention has been focused on other stages of the GP recruitment pipeline,29 but it is important that the experiences GP trainees encounter during their secondary care placements are also considered as a potential source of discontent. On this point, our findings add to those of Spooner et al , whose research on career intentions of new UK GPs found that many felt that hospital placements had done ‘little to prepare them for GP work’ 12…”
Section: Discussionsupporting
confidence: 76%
“…Our participants felt that educationally fulfilling LTFTW options were less accessible to them in secondary care placements than in primary care. Such issues may relate to senior staff in hospital settings prioritising service delivery or the needs of trainees in secondary care specialty training programmes 12. With increasing numbers of trainees having family and caring commitments, and fewer trainees following linear or direct pathways through to completion of training, prioritising flexibility could help improve job satisfaction and retain trainees in the workforce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly commended A study led by Dr Sharon Spooner in Manchester titled 'The influence of training experiences on career intentions of the future GP workforce: a qualitative study of new GPs in England', 4 was 'highly commended' by Panel 3. Dr Spooner reflects:…”
Section: Medical Education With Relevance To Primary Care -Winnermentioning
confidence: 99%
“…15 Workforce modelling indicates a continuing projected shortage of GPs and practice nurses. [19][20][21] An insufficient number of GPs will be available as a result of historic recruitment deficits and poor career retention, [22][23][24][25] and there has been little increase in the number of nurses. 26 Increasing workloads have led to government policy changes including recent recommendations regarding the deployment of a broader range of practitioner types.…”
mentioning
confidence: 99%